The following two-step process has equilibrium constants K1 and K2. Step 1: H2(g) + ICl(g) → HI(g) + HCl(g) K1 Step 2: HI(g) + ICl(g) → HCl(g) + I2(g) K2 Overall : H2(g) + 2ICl(g) → 2HCl(g) + I2(g) K3 What is the expression for the equilibrium constants for the overall reaction, K3?

Respuesta :

Answer : The equilibrium constant expression for overall reaction will be:

[tex]K_3=K_1\times K_2[/tex]

Explanation:

The given chemical reactions are:

Step 1 : [tex]H_2(g)+ICl(g)\rightarrow HI(g)+HCl(g)[/tex];   [tex]K_1[/tex]

Step 2 : [tex]HI(g)+ICl(g)\rightarrow HCl(g)+I_2(g)[/tex];    [tex]K_2[/tex]

Overall : [tex]H_2(g)+2ICl(g)\rightarrow 2HCl(g)+I_2(g)[/tex];   [tex]K_3[/tex]

By the addition of reaction 1 and reaction 2, we get the overall reaction.

As we know that, when we are adding reactions then their equilibrium constant will be multiplied.

Thus, the equilibrium constant expression for overall reaction will be:

[tex]K_3=K_1\times K_2[/tex]